Upgrading of gamma cameras for developing countries - Fidler, Valentin (Radiology and oncology (Ljubljana), 2001)
Background. The project of upgrading the analog gamma cameras with PC based systems from International Atomic Energy Agency (IAEA) and the Ministry of Science and Technology of RS is presented from the initial basic deman the final developments. Several national research groups (from China, India, Cuba and Slovenia) were involved in the IAEA development project for the acquisition card with software and the standard set of clinical protocols. Conclusions. The most functionally stable acquisition system tested on severalinternational workshops and in university clinics was the Slovenian onewith a complete set of nuclear medicine clinical protocols, documenting, networking and archiving solutions for simple MS Network or server oriented network systems (NT server, etc). More than 300 gamma cameras in 52 countries all over the world were digitized and put in routine clinical work.
Keywords: diagnostika; projekti